(untitled) - N. Vinay Kumar; T. S. Gugapriya (Academia Anatomica International, 2018)
Introduction: The environment of middle ear cavity gets regulated mostly by pneumatized mastoid air cell system (MACS). Many theories exist that details the process of pneumatization of this MACS. The nasal septal deviation (NSD) has been shown to be instrumental in influencing pneumatization of paranasal sinuses to varied degrees. The effect of NSD on the pneumatization of MACS remains questionable due to limited literature available. And so this study was done to find the relation between the side of NSD and extent of Pneumatization of MACS on that side by computerized tomographs of Paranasal sinus region. Subjects and Methods: 120 CT images of paranasal region from archives of radiology department were studied for NSD. The NSD was classified according to the nasal septal angle. The extent of pneumatization of mastoid region was studied and classified. The relation between severe NSD and extent of mastoid pneumatization was noted. Results: NSD was found to be right sided in 90% cases studied and 20, 45, 55 were seen belonging to group I, II and III NSD respectively. The mean NSA was found to be 13.5o.  Mastoid region was observed to be hypo pneumatized in the side of NSD in 42 cases of group III NSD. Conclusion: The findings of the study puts forth the need for assessment of NSD and planning possible correction of NSD prior to middle ear and mastoid surgeries for successful results.